Dialogic Foundations of the “4-trans” Framework: Towards a Comprehensive and Dynamic Understanding of Multilingual Teacher Education - Martínez-Prieto, David; Musanti, Sandra; Zhou, Xiaodi (International Journal of Multicultural Education, 2025)
In this article, we develop the “4-trans” framework by reflecting on the way current multilingual teacher preparation scholarship has addressed translanguaging, transnationalism, transculturality, and transdisciplinarity either in compartmentalized or integrative manners. While current literature has addressed some “trans” intersections, we propose the enunciation of the “4-trans” as permeable and complementary principles in multilingual education that can serve to better examine the experiences and challenges of multilingual pre-service teachers. To amalgamate the “4-trans” to examine the development of multilingual pre-service teachers, this article describes the construction of a multidimensional framework based on a dialogic conception of social mediation, heteroglossia, and critical consciousness.